Fresno Chapter of Women's International League for Peace and Freedom Celebrating Louise Erickson and Marcia McLane - Watkins, Howard::::::::: (1989)
Linda Mack, Lindell Cross, Louise Erickson, Victor McLane and Marcia McLane at Pat Wolk's Garden